2004
DOI: 10.1143/jjap.43.5122
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous/Microcrystalline Silicon Thin Film Transistor Characteristics for Large Size Oled Television Driving

Abstract: An amorphous silicon thin film transistor (TFT) and a TFT with a microcrystalline/amorphous channel layer are studied for organic light emitting diode (OLED) backplane usage. The amorphous silicon TFT V TH shift can be reduced with saturation region operation. There are two mechanisms that cause the V TH shift in a saturation region: One that appears with continuous current flow and the other that appears with the transient charge injection into a gate insulator. SiH 4 flow in hydrogen plasma with a pumping fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…For example, the threshold voltage shift of a-Si:H TFT is still a serious issue for OLED displays. 13) The degradation mechanisms in a-Si:H TFTs under bias-temperature (BT) and drain current stresses have been studied extensively. [13][14][15][16] Based on these studies, electrical and environmental stabilities of oxide TFTs have been investigated very recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the threshold voltage shift of a-Si:H TFT is still a serious issue for OLED displays. 13) The degradation mechanisms in a-Si:H TFTs under bias-temperature (BT) and drain current stresses have been studied extensively. [13][14][15][16] Based on these studies, electrical and environmental stabilities of oxide TFTs have been investigated very recently.…”
Section: Introductionmentioning
confidence: 99%
“…13) The degradation mechanisms in a-Si:H TFTs under bias-temperature (BT) and drain current stresses have been studied extensively. [13][14][15][16] Based on these studies, electrical and environmental stabilities of oxide TFTs have been investigated very recently. [17][18][19][20][21][22][23][24][25][26]28) It was reported that negative charge trapping in an oxide semiconductor and its interface with a gate insulator or charge trapping in a gate insulator plays important roles in determining positive BT instability of oxide TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a challenge, complementary to oxide semiconductor research, especially on plastic, is to identify a gate dielectric material and process that enable low voltage operation, reliability and stability with low device off-state current. Active electronic identification tags, for example, need sub-5 V operation [4], and OLEDs require high drive currents at typically less than 10 V [10]. For active-matrix driven LCDs, the static off-state current should be 0.1-1.0 pA [8].…”
Section: Overviewmentioning
confidence: 99%
“…Thin-film manufacturing methods using gas mixtures consisting of two or more gases such as SiH 4 -CH 4 and CH 4 -H 2 are used for the production of thin-film transistors and various other electronic devices, and of diamonds and other industrial products [1,2]. Among these methods, the gas decomposition method using a radio frequency glow discharge is often used for the manufacture of amorphous silicon semiconductor thin films because of its excellent control of plasma parameters and the potential for expansion of the film surface areas [3,4].…”
Section: Introductionmentioning
confidence: 99%